2007
DOI: 10.1210/en.2007-0126
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Cytokine Activation of Apoptosis Pathways in the Thyroid

Abstract: It has been suggested that Fas-mediated apoptosis plays an important role in the pathogenesis of autoimmune thyroid diseases. Our previous studies have demonstrated that normal primary thyroid epithelial cells are resistant to Fas-mediated apoptosis, but the resistance can be overcome by pretreatment with a combination of interferon-gamma (IFN-gamma) and IL-1beta. To understand the molecular mechanism responsible for the IFN-gamma/IL-1beta effects, we profiled changes in the transcription induced by these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…Some studies suggested that TRAIL suppresses the development of autoimmune thyroiditis [32,33]; others considered that apoptosis induced by TRAIL and DR5 can promote the development of autoimmune thyroiditis [34][35][36]. In our study, we found that TRAIL and DR5 promoted follicular cells apoptosis, thus mediating thyroid destruction in experimental autoimmune thyroiditis (EAT), and activated immune cells play an important role during the inflammatory response.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some studies suggested that TRAIL suppresses the development of autoimmune thyroiditis [32,33]; others considered that apoptosis induced by TRAIL and DR5 can promote the development of autoimmune thyroiditis [34][35][36]. In our study, we found that TRAIL and DR5 promoted follicular cells apoptosis, thus mediating thyroid destruction in experimental autoimmune thyroiditis (EAT), and activated immune cells play an important role during the inflammatory response.…”
Section: Introductionsupporting
confidence: 54%
“…Activated immune cells may be responsible for inducing thyroid cell destruction during the inflammatory response by producing inflammatory cytokines, and increasing the local production of inflammatory cytokines in the thyroid microenviroment plays a critical role in facilitating thyrocyte apoptosis [34][35][36]. Potential models for the involvement of TRAIL in autoimmune destructive thyroiditis include the following: (a) cytokines produced by activated immune cells induce thyroid cell susceptibility to TRAIL, and immune cells expressing TRAIL can subsequently kill thyroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thyrocytes expressing Bcl-2 can be more resistant to Fas-mediated cell death 1 4 16. Fas-mediated apoptosis may include the activation of a variety of caspases such as caspases 1, 2, 3, 7, 8, 9, 10 3 10 18. The Fas pathway is the most important mechanism of T lymphocyte mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both proliferation and apoptosis are involved in the pathogenesis of Hashimoto disease. The latter can be activated by a wide variety of external or internal stimuli 1 3…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of autoimmune thyroiditis is not entirely clear, studies have demonstrated that increasing the local production of inflammatory cytokines in the thyroid microenvironment plays a critical role in facilitating apoptosis in thyrocytes, leading to autoimmune thyroiditis [1-3]. Among various inflammatory cytokines, IFN-γ, TNF-α and IL-1β appear to be critical since the combination of two such cytokines can significantly facilitate the development of experimental autoimmune thyroiditis (EAT) in mice [1,3,4], a well-recognized animal model of autoimmune thyroiditis.…”
Section: Introductionmentioning
confidence: 99%